Christian Faith and AI: A Theological-Philosophical Analysis and its Relevance to the Existence of the Catholic Church - Agustinus Abraham (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2026)
This study analyzes the relationship between Christian faith and artificial intelligence (AI) through a theological-philosophical approach and assesses its relevance to the existence of the Catholic Church in the digital age. The background of this study stems from the rapid development of AI, which brings both opportunities and risks to the life of faith, such as the simplification of theological teachings, the reduction of personal relationships, and the emergence of a technocratic paradigm. The study uses qualitative methods with a literature review of the Holy Scriptures, Church documents, and literature on philosophy and technology ethics. The results of the analysis show that AI is a product of human creativity as the image of God, so it does not conflict with faith, but it remains instrumental and does not have moral or spiritual dimensions like humans. Therefore, AI cannot replace the role of humans in faith relationships. The Church is called to guide technological development through Christian ethical principles, upholding human dignity, being critical of the effects of dehumanization, and utilizing AI wisely for evangelization, catechesis, and faith education. With a reflective and critical approach, the Church can remain relevant amid technological advances without losing its identity and mission for the common good.